Modern And Traditional Speech Teaching Technologies - Mamatkulova Gulxayo (Zien Journals, 2022)
This article provides information on the relevance of the problem of speech production today and the use of pedagogical technologies in speech production, scientific ideas, rules, types of methods.
Keywords: Speech; technology; pedagogical; traditional